The role of compaction energy in increasing the bearing capacity of paving layers constructed from recycled materials from concrete demolition rubble - حنا, رامي (Latakia University Journal -Engineering Sciences Series, 2024)
In the last twenty years, the phenomenon of using recycled materials from demolition rubble (especially materials from the products of recycling concrete rubble) has spread in the construction of road paving layers, whether in flexible road pavement or solid pavement. The recycled aggregates from the products of concrete demolition may have geotechnical and engineering properties. Various, some of them limit their use in creating the base layer, including maximum dry density, relative bearing capacity, C.B.R, and Los Angeles wear. In our research, we tested the development of the maximum dry density and the bearing capacity of the C.B.R depending on the applied energy, which in turn gave good results, as the maximum dry density increased by 18% when a number of strokes of 65 were applied to each of the five layers forming the Proctor mold, which was offset by an increase in the relative bearing capacity. The C.B.R. by 23%. However, the maximum increase rates for these materials stopped increasing steadily with the number of blows (70-75) blows, meaning that the increase reached 5.7% for the maximum dry density and 82.1% for the relative bearing capacity of the C.B.R.